2011
DOI: 10.1074/jbc.m111.296103
|View full text |Cite
|
Sign up to set email alerts
|

Single Molecule Fluorescence Study of the Bacillus thuringiensis Toxin Cry1Aa Reveals Tetramerization

Abstract: Background:The stoichiometry of pore-forming toxins is frequently unknown because crystal structures do not reflect the active conformations. Results: We used single subunit counting on fluorescently labeled Cry1Aa toxin of Bacillus thuringiensis to follow its oligomerization process. Conclusion: We determined that the final architecture of the pores is tetrameric. Significance: The stochastic analysis introduced permits the application of single subunit counting to dynamic processes such as oligomerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 59 publications
0
40
0
Order By: Relevance
“…We therefore employed TIRF microscopy and single molecule photobleaching (30,40,41) to determine the stoichiometry of homo-and hetero-oligomers formed by PopB and PopD inserted in membranes. These experiments clearly showed that a unique hetero-oligomer is formed when PopB and PopD are added together.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore employed TIRF microscopy and single molecule photobleaching (30,40,41) to determine the stoichiometry of homo-and hetero-oligomers formed by PopB and PopD inserted in membranes. These experiments clearly showed that a unique hetero-oligomer is formed when PopB and PopD are added together.…”
Section: Discussionmentioning
confidence: 99%
“…We adapted the technique to quantify proteins in their native lipid bilayer environment (i.e. in the absence of detergents) by using SLB (30). PopB BpyFL or PopD BpyFL were reconstituted into liposomes using previously optimized conditions for membrane association and pore formation (14).…”
Section: Popb Assists the Association Of Popd With Membranes-bothmentioning
confidence: 99%
“…Alternatively, the activated toxins could individually insert into the target membrane, where they subsequently assemble into an oligomeric pore complex, causing cell lysis (13,20). However, the precise molecular description of either model still remains to be critically verified.…”
mentioning
confidence: 99%
“…However, we cannot rule out the possibility that buried disulfide bridges may not be exposed to the reducing environment of the midgut lumen. In this case, a plausible explanation is that the entire domain I inserts into membrane as previously proposed, either as a whole protein [7,[12][13][14][15][16][17] or as a member of an oligomeric complex [18,23,35,36]. This would also result in no difference in toxicity between the wild-type and disulfide proteins.…”
Section: Discussionmentioning
confidence: 70%
“…Several disulfide-bridge mutations generated by protein engineering which are related to the membrane partitioning mechanisms of Cry toxins are reviewed in [21]. An intermediate step has been proposed in which the oligomerization occurs in tetramers after the hairpins from α-helices 3 and 4 are inserted into the membrane [22,23]. At the present time no single model can account for all the experimental observations.…”
Section: Introductionmentioning
confidence: 99%